Book review: Flipped Classrooms for Legal Education, 1st ed. Lutz-Christian Wolff, Jenny Chan, Springer. (January 2020) - Yadav, Manish
Flipped Classrooms for Legal Education, 1st ed. Lutz-Christian Wolff, Jenny Chan, Springer, 2016 (Paperback).